Tree Diversity, Conservation Status and Utilization Potentials of Shasha Rainforest Reserve, Southwestern, Nigeria - Akinyemi, O.D; Oloketuyi, A.J; Akinyemi, G.O; Adeoye, O.T; Aina-Oduntan, O.A; Olatidoye, O.R (Journal of Forests, 2021)
An inventory of the entire tree species ≥10cm diameter at breast height (dbh) was carried out within Forestry Research Institute of Nigeria (FRIN) investigation 133 Shasha in Osun State, Nigeria. This study was carried out to ascertain the tree species diversity, conservation status and utilization potentials in the study area. The results were obtained from 16 sample plots of 50×50m in four tracts located through cluster sampling technique. In all, an average total of 295 stands distributed among 66 tree species and 28 families were encountered. High value of Shannon-Weinner index H'=3.73 and Evenness of E=0.89 were obtained for the reserve. At present, only few trees have attained the merchantable size of 48cm dbh. The 63 tree species in the study site were categorized into four groups namely, stable, vulnerable, endangered and threatened status. The result revealed that stable group had 1.59%, vulnerable 4.76%, endangered 44.44% and threatened 49.21%. Result of the Utilization potentials revealed that utility classes 7 - 8 accounted for 55.6% (comprises of tree species with no potential use for sawn timber), while 45.4%. of trees in classes 1 – 6 comprises of trees with timber potentials. This study highlighted species population diversity, conservation status and utilization potentials of the study site and called for ecological application in the management of forest reserves in Nigeria.